You are a bad ass how to stop doubting your greatness and start living an awesome life - Sincero, Jen 1965-
You are a badass is the self-help book for people who desperately want to improve their lives but don't want to get busted doing it. In this refreshingly entertaining how-to guide, best selling author and world-traveling success coach, Jen Sincero, serves up 27 bite-sized chapters full of hilariously inspiring stories, sage advice, easy exercises, and the occasional swear word, helping you to: identify and change the self-sabotaging beliefs and behaviors that stop you from getting what you want; create a life you totally love. And create it now.; make some damn money already. The kind you've never made before